2023
DOI: 10.3389/fendo.2023.1216817
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the role of the Wnt signaling pathway in pituitary adenoma

Wencai Wang,
Luyao Ma,
Yongqiang Zhao
et al.

Abstract: Pituitary adenoma (PA) is the third most common central nervous system tumor originating from the anterior pituitary, but its pathogenesis remains unclear. The Wnt signaling pathway is a conserved pathway involved in cell proliferation, Self-renewal of stem cells, and cell differentiation. It is related to the occurrence of various tumors, including PA. This article reviews the latest developments in Wnt pathway inhibitors and pathway-targeted drugs. It discusses the possibility of combining Wnt pathway inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Dysregulation of this pathway often arises from mutations in various components, particularly mutations or silencing of Wnt tumor suppressors, with mutations in β-catenin being the most commonly observed alterations in cancer [30]. Aberrant Wnt/β-catenin signaling is closely associated with the development of numerous tumors, including PitNETs [31]. Gaston-Massuet et al [32] found that the expression of mutated β-catenin leads to a significant increase in the total number and proliferative potential of pituitary progenitor/stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of this pathway often arises from mutations in various components, particularly mutations or silencing of Wnt tumor suppressors, with mutations in β-catenin being the most commonly observed alterations in cancer [30]. Aberrant Wnt/β-catenin signaling is closely associated with the development of numerous tumors, including PitNETs [31]. Gaston-Massuet et al [32] found that the expression of mutated β-catenin leads to a significant increase in the total number and proliferative potential of pituitary progenitor/stem cells.…”
Section: Discussionmentioning
confidence: 99%